Integrated Community Case Management Utilization Status and Associated Factors Among Caretakers of Sick Children Under the Age of 5 Years in West Shewa, Ethiopia - Lemessa Negeri Debel; Fikadu Tadesse Nigusso (Frontiers Media S.A., 2022)
ObjectiveTo assess the utilization status and associated factors of integrated community case management (ICCM) of caretakers with <5 years of sick children.MethodsCommunity-based cross-sectional study was employed with caretakers whose child was sick in the last 3 months before data collection. Bivariate and multivariable logistic regression analyses were employed.ResultsAbout 624 respondents participated in the study; 325 (52.1%) utilized integrated community case management. Caring for children between the ages 24-36 months old, (AOR = 1.26, 95%CI: 0.23, 0.90); women health development army (WHDA) training, (AOR = 5.76, 95%CI: 3.57, 9.30); certified as model family, (AOR = 3.98, 95%CI: 2.45, 6.46); perceived severity, (AOR = 5.29, 95%CI: 2.64, 10.60); awareness of danger sign, (AOR = 2.76, 95%CI: 1.69, 4.50), and awareness of ICCM, (AOR = 5.42, 95%CI: 1.67, 17.58) were associated with ICCM utilization.ConclusionThis study revealed that age of the child, caretakers' awareness of ICCM, awareness of danger signs, illness severity, women's health developmental army training, and graduation as a model family were associated with ICCM utilization. Therefore, it is recommended that promote health education using community-level intervention modalities focusing on common childhood illness symptoms, danger signs, severity, and care-seeking behavior.